Pseudotemporal invitations: 6- to 9-year-old maltreated children’s tendency to misinterpret invitations referencing "time" as solely requesting conventional temporal information - McWilliams, Kelly (Child maltreatment, 2023)
Forensic interviewers ask children broad input-free recall questions about individual episodes in order to elicit complete narratives, often asking about “the first time,” “the last time,” and “one time.” An overlooked problem is that the word “time” is potentially ambiguous, referring both to a particular episode and to conventional temporal information. We examined 191 6-9-year-old maltreated children’s responses to questions about recent events varying the wording of the invitations, either asking children to “tell me about” or “tell me what happened” one time/the first time/the last time the child experienced recent recurrent events. Additionally, half of the children were asked a series of “when” questions about recurrent events before the invitations. Children were several times more likely to provide exclusively conventional temporal information to “tell me about” invitations compared to “tell me what happened” invitations, and asking “when” questions before the invitations increased children’s tendency to give exclusively conventional temporal information. Children who answered a higher proportion of “when” questions with conventional temporal information were also more likely to do so in response to the invitations. The results suggest that children may often fail to provide narrative information because they misinterpret invitations using the word “time”.